Effects of seed inoculation with Hartmannibacter diazotrophicus on indigenous bacterial communities in the rhizosphere and on plant yield parameters in wheat and barley over three seasons - Quiroga Quisaguano, Santiago Andres; Justus Liebig University Giessen (My University, 2025)
The use of mineral fertilizers and pesticides is not allowed in organic farming, which can reduce the yield and grain quality of cereals. In recent years, the potential of plant growth-promoting rhizobacteria (PGPR) has been recognized for a better supply of nutrients and improved resilience to abiotic and biotic plant stress. Although the mechanisms of PGPR are well studied, their effectiveness under field conditions is not consistent. There is also limited information on the effects of the use of allochthonous microorganisms on the native soil microbiome. In this study, we evaluated the effects of seed inoculation with Hartmannibacter diazotrophicus strain E19T on the rhizosphere bacterial communities of wheat and barley by analyzing community changes by the strain using metabarcoding and subsequent bioinformatic evaluation. This analysis was performed at two experimental stations (Gladbacherhof and Kleinhohenheim) for organic farming in three seasons (2021-2023). For this purpose, DNA and RNA were extracted from the rhizosphere soil, the 16S rRNA gene sequences or the 16S rRNA were sequenced and analyzed bioinformatically. The effects of different row spacing and the application of organic fertilizer on winter wheat were also tested. The occurrence of H. diazotrophicus strain E19T was quantified by real-time PCR at the flowering and milk-ripe/yellow-ripe stages. In order to determine the influence of the various factors (with/without seed inoculation, different row spacing, and with/without fertilization on winter wheat) on the plant, the grain and straw yield, as well as the crude protein concentration of the grains were recorded. H. diazotrophicus strain E19T was detected 273 and 119 days after sowing on both wheat roots (up to 3.1 x 10^5 copies g^-1 DW) and barley roots (up to 5 x 10^5 copies g^-1 DW) mainly at one experimental station. The abundance of H. diazotrophicus strain E19T was correlated with yield parameters using linear mixed models. Significant effects were found for crude protein concentration (0.80% higher in barley and 0.30% higher in wheat compared to the average) and straw yield (453 kg ha^-1 higher in wheat compared to the average). Although no significant effects on grain yield were found, a trend towards improvement was observed with the combination of organic fertilizer and bacterial inoculation. Interestingly, H. diazotrophicus strain E19T did not change the rhizosphere community structure over three seasons. These results were based on a comparison of beta-diversity indices (Robust Aitchison Principal Component Analysis) with subsequent statistical analysis using PERMANOVA (p > 0.05). Similarly, alpha diversity indices, including Shannon-Wiener, observed amplicon sequence variants (ASVs) and Gini-Simpson (Wilcoxon, p > 0.05) showed no significant effects. Similar results were found after extraction of environmental RNA compared to DNA and its sequencing and bioinformatic analysis. These results indicate that the indigenous bacterial rhizosphere communities were resilient to newly introduced bacteria after seed inoculation with H. diazotrophicus strain E19T. The strongest changes in the bacterial community were identified between the two locations as shown by differential abundance analysis (ALDEx2). The ALDEx2 analysis identified 2860 ASVs that were different between winter wheat and spring barley at the Gladbacherhof site, while only 232 ASVs were different between these crops at Kleinhohenheim. These differences could be due to the different crop rotations at the two sites.
Keywords: ddc:630